2x

When dealing with quadratic expressions the standard form is ax

The factor format is (mx + n)(px + q). In this question a = 2, b = -3y, c = -2y

The technicalities can be covered later but basically permutate the product of the factors of

As a = 2 the factors are 1,2.

As c = -2y

The permutations are 1 x -y, 2 x 2y, sum 3y: 1 x 2y, 2 x -y, sum 0. Neither combination produces the sum -3y but the first pairing produces 3y. So, by working with the 'reverse' factors we have 1 x y, 2 x -2y, sum -3y which is the desired result.

^{2}- 3xy - 2y^{2}= (2x + y)(x - 2y)When dealing with quadratic expressions the standard form is ax

^{2}+ bx + c.The factor format is (mx + n)(px + q). In this question a = 2, b = -3y, c = -2y

^{2}.The technicalities can be covered later but basically permutate the product of the factors of

*a*with those of*c*so that the sum generates the value of*b*(= -3y).As a = 2 the factors are 1,2.

As c = -2y

^{2}the factors are -y,2y, (the reverse also applies eg -2y,y)The permutations are 1 x -y, 2 x 2y, sum 3y: 1 x 2y, 2 x -y, sum 0. Neither combination produces the sum -3y but the first pairing produces 3y. So, by working with the 'reverse' factors we have 1 x y, 2 x -2y, sum -3y which is the desired result.